Analisis Pencatatan Dan Pelaporan Keuangan Satuan Kerja Perangkat Daerah (SKPD) Pada Dinas Sosial Kabupaten Ende - Aos, Yuliana Chamsentya; Reo, Hermanus; Soleiman, Iriany Dewi (Jurnal Riset Ilmu Akuntansi, 2021)
Each Regional Work Unit (SKPD) carries out accounting for economic transactions that occur on its part, to produce financial reports. The purpose of this study was to analyze the suitability of SKPD financial recording and reporting in Ende Regency, especially the Social Service with Permendagri Number 21 of 2011 and Government Regulation Number 71 of 2010. This research uses descriptive qualitative. This writing uses data collection techniques, namely field studies and literature studies. The results showed that the Social Service of Ende Regency had not kept records in accordance with the Regulation of the Minister of Home Affairs Number 21 of 2011 concerning Guidelines for Regional Financial Management related to a recording error in the ledger, namely the employee expenditure ledger, which should have been recorded at IDR 1,878,849,154 but it was recorded at IDR 1,878. .938,674 and there are still obstacles, namely limited human resources in carrying out activities according to their fields and still lack of technical support facilities and infrastructure for activities.